A Feasibility study on Zeolites - Gonzales, Caryn O.; Moncada, Marchae Gizette B.; Quesada, John Paul. (Diliman, Quezon City College of Engineering, 1996)
The purpose of this study is to assess the feasibility of a project venture which will produce zeolites made from Mt. Pinatubo ejecta, better known as lahar. The product was developed by the Materials Science Division of the Department of Science and Technology. There is no local manufacturer of zeolites. Zeolites used by the local industdes are sourced from other countries, mostly in the Asian region. From the market study, demand for zeolites was obtained. In 1997, the project's initial year, the demand for zeolites is estimated to be 5,722,897 kg. This is projected to increase in the next four years. It was also found in the market study that the major user of zeolites in the Philippines is the detergent industry. The project venture has a market share of 80.72% which constitutes the demand (or a pari of it) of the three biggest detergent companies in the country. With this, the company intends to have these companies as its target market. As a marketing strategy, the company will price its environmentally friendly product lower than the price of imported zeolites and will position itself as a company who delivers its product fast. In the technical study, it was found that the product can be manufactured. Also, other raw materials of the product were found to be available in the local market including the required machines and equipment. A suitable factory location was found along Llano Road, in Caloocan City, which is midway the source of raw materials and the project's target customers. The project will have an initial investment cost of P45,927,085. A financial analysis was then conducted and it showed that the venture is financially profitable. It has an Internal Rate of Return of 56.97% and net income for the first year amounted to P26,440,905.02 which is projected to increase in the next four years. Also, using widely used socio-economic criteria, a social profitability study was conducted and it showed that the venture provides a positive gain in the economy, and is thus socialy profitable. To serve as a guide for project implementation, an organization and management study was conducted. In this study, an organizational structure that would best suit the scale and operations of the project was designed. It was also determined that the company shall have a partnership type of ownership and a total workforce of 61, which includes both direct and indirect labor.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: Chemical industry; Zeolites; Participatory monitoring and evaluation (Project management)